Essential VCD business management : - Somers, Gillian (Cambridge University Press, 2004)
This resource contains: • Editable chapter tests - that assist with revision and consolidation of learning • A range of outcome tasks - written to meet all areas of study and which can be edited to meet the needs of classrooms • Unit 1 & 2 practice exams - that can be used for assessment or revision.